Composition and Profile of Fatty Acids in Milk on Quality and Health - -, Rosidi Azis; -, Juniarti Wulan Lestari; -, Aridatuz Zahroh (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2025)
The fatty acid (FA) profile of bovine milk is a dynamic compositional trait that serves as a pivotal determinant of both dairy product quality and human health outcomes. Historically scrutinized for its saturated fat content, contemporary research reveals milk fat as a complex source of diverse lipids, including beneficial trans fatty acids, odd-chain saturated fatty acids, and conjugated linoleic acid (CLA). This review synthesizes current knowledge on the composition, key dietary determinants, and dual consequences of the milk FA profile. It demonstrates that ruminant nutrition, particularly pasture-based feeding and lipid supplementation, is the primary lever for modifying this profile, enhancing bioactive components while simultaneously altering the physicochemical properties of the fat. The analysis positions the FA profile as a functional hinge, where improvements in nutritional value such as increased omega-3 FAs and CLA often conflict with technological quality parameters like oxidative stability and texture. A critical reevaluation of health impacts dismantles the simplistic view of milk saturated fats, underscoring the heterogeneous metabolic effects of individual fatty acids and the significance of the whole-food dairy matrix. Ultimately, navigating this hinge necessitates an integrated approach combining tailored animal nutrition, innovative processing, and evidence-based dietary guidance to harness milk fat's full potential. This synthesis provides a foundational resource for developing dairy products that align optimal sensory and functional characteristics with enhanced human health benefits, moving beyond reductionist paradigms towards a holistic understanding of milk fat.